1964
DOI: 10.1084/jem.119.2.303
|View full text |Cite
|
Sign up to set email alerts
|

The Application of Tissue Culture to the Study of Experimental Allergic Encephalomyelitis

Abstract: Myelinated cultures of rat and mouse cerebellum undergo a specific and characteristic pattern of demyelination in the presence of sera from animals with experimental allergic encephalomyelitis (EAE) (1, 2). The neuroglia swell; myelin sheaths become disfigured b y fusiform swellings and break away as small fragments; and finally, remaining intact sheaths and myelin fragments are reduced to small fat droplets. During this process neuron somas and axons appear little affected (Figs. 1 to 4).This communication wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

1971
1971
2008
2008

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(22 citation statements)
references
References 13 publications
1
21
0
Order By: Relevance
“…In particular IgG2a demonstrated increases greater than six fold. The observation that the IgG fraction of serum can produce complement-dependent demyelination in experimental models (Appel and Bornstein, 1961;Halstead et al, 2005;Saida et al, 1979) raises the question as to whether the elevation in IgGs could represent an autoimmune component in DEDC myelinopathy. Autoantibodies could possibly be produced from the generation of non-self oxidatively damaged proteins or from release of normally sequestered nerve proteins into the general circulation.…”
Section: Discussionmentioning
confidence: 99%
“…In particular IgG2a demonstrated increases greater than six fold. The observation that the IgG fraction of serum can produce complement-dependent demyelination in experimental models (Appel and Bornstein, 1961;Halstead et al, 2005;Saida et al, 1979) raises the question as to whether the elevation in IgGs could represent an autoimmune component in DEDC myelinopathy. Autoantibodies could possibly be produced from the generation of non-self oxidatively damaged proteins or from release of normally sequestered nerve proteins into the general circulation.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies have supported evidence for an anti-myelin antibody role in MS and EAE demyelination (Appel and Bornstein, 1964;Seil et al, 1968;Kim et al, 1970;Raine et al, 1973). Serum from animals with EAE as a result of immunization with whole myelin causes myelin breakdown through complement-and antibodydependent mechanisms (reviewed by Raine, 1984b).…”
Section: Introductionmentioning
confidence: 99%
“…Early in vitro models of demyelination using cerebellar cultures showed that the demyelinating component of sera from animals with EAE was heat labile, a classical characteristic of the complement system (8). In rat EAE, complement depletion ameliorates disease (9), and in a demyelinating model, Ab-mediated demyelinating EAE (ADEAE), induced by injection of Abs to myelin oligodendrocyte glycoprotein (MOG) at the onset of clinical signs in EAE (10), complement is essential for demyelination (11,12).…”
mentioning
confidence: 99%